Viability Analysis of Waste Tires as Material for Rail Vibration and Noise Control in Modern Tram Track Systems - Caiyou Zhao; Ping Wang; Qiang Yi; Duo Meng (Shock and Vibration)
This research study focused on the effect of using damping chamber elements made from waste tires on railway noise reduction. First, the energy absorption characteristics of damping chamber elements with various gradation combinations and compaction indices were measured in the laboratory using compression testing. The laboratory compression results demonstrated that the optimal gradation combination of damping chamber elements is as follows: the content of fine rubber particles is 10%, the content of coarse granules is 90%, and the optimal compaction index is 0.98. Next, the findings from the laboratory compression-test studies were used to produce damping chamber elements that were applied to a full-scale modern track model in the laboratory. The measurements of the dynamic properties indicated that the damping chamber elements could significantly reduce the vibration levels of the rail head. Finally, the damping chamber elements, which had been proven effective through laboratory dynamic tests, were widely applied to test rail sections in the field. The field tests demonstrated that damping chamber elements can significantly increase the track vibration decay rate in the frequency range of 200–10000 Hz. Therefore, damping chamber elements made from waste tires are able to control rail vibration and noise in modern tram track systems.